Mesozoic resource potential in the southern Permian Basin - Kilhams, B. (Ben); Kukla, Peter A.; Mazur, S. (Stan); McKie, T. (Tom); Mijnlieff, H. F.; Ojik, K. van (Geological Society special publication, 2018)
The Southern Permian Basin, as its name suggests, is a historical heartland for hydrocarbon production from the Palaeozoic Rotliegend interval. However, in this mature basin the Mesozoic presents further possibilities to offer resource security to NW Europe. Such opportunities include increasing efficiency in the production of discovered hydrocarbons, exploration for further hydrocarbons (both conventional and unconventional) and efficient exploration for, and production of, geothermal energy. All these potential resources require a grounding in technically sound geoscience, via traditional scientific observation and the application of new technologies, to unlock their value. The main aim of this volume is to bring together the work of academics and industry workers to consider cross-border geoscience including contributions on Poland, Germany, The Netherlands, the United Kingdom and adjacent areas. The work presented intends to contribute to the development and discovery of further Mesozoic energy resources across the basin.